High-affinity uptake of noradrenaline in quail dorsal root ganglion cells that express tyrosine hydroxylase immunoreactivity in vitro - Xue, ZG (J Neurosci, 1988)
During embryonic life, avian sensory ganglia contain cells with the potential to express, under appropriate experimental conditions, a number of properties characteristic of autonomic sympathetic neurons. Thus, cells capable of synthesizing noradrenaline (NA) from tyrosine differentiate when dorsal root ganglia (DRG) from 10–15 d embryonic quail are grown in culture (Xue et al., 1985a, b). In the present study, we show that cultures of DRG from 10 d embryos can take up 3H-NA by a high-affinity (Km = 1.0 microM), temperature-dependent process that can be inhibited by desmethylimipramine. By means of combined immunocytochemistry and autoradiography, it was demonstrated that the majority (70–80%) of the tyrosine hydroxylase (TH)-immunoreactive cells that developed in the cultures possessed a transport system for NA. Catecholamine (CA) uptake also occurred in a small, but relatively constant, number of TH-negative cells, but was absent from substance P- containing neurons. In contrast to TH, which appears only after 3–4 d in vitro, cells capable of taking up NA with high affinity were found in DRG cultures after only a few hours, and a small number (less than 0.5% of the total cell population) was detected in freshly removed, uncultured ganglia. Such cells did not react with antibodies directed against substance P or neurofilament proteins. We conclude that autonomic precursors are identifiable in a subset of non-neuronal DRG cells, prior to full expression of a noradrenergic phenotype, by their possession of a high-affinity uptake system for CA.